The Dimensioning of a Compressed Air Motor Dedicated to a Compressed Air Storage System - Ilham Rais; Hassane Mahmoudi (Institute of Advanced Engineering and Science, 2018)
Storage represents the key to the penetration of renewable energies especially wind and solar energy on the network electric. It avoids unloading in the event of overproduction, ensuring real-time The production-consumption balance and also improve the robustness of the electricity grid. CAES (Compressed Air Energy Storage) is a mature technology that allows to store long or short duration an amount of energy sucient to support the number of cycles requested. The E-PV-CAES system will be presented and the modeling of the compressed air engine will also be treated in more detail in this article.